Synthetic hemoglobin‐based oxygen carriers are an acceptable alternative for packed red blood cells in normothermic kidney perfusion. Issue 10 (26th April 2019) - Aburawi, Mohamed M.; Fontan, Fermin M.; Karimian, Negin; Eymard, Corey; Cronin, Stephanie; Pendexter, Casie; Nagpal, Sonal; Banik, Peony; Ozer, Sinan; Mahboub, Paria; Delmonico, Francis L.; Yeh, Heidi; et al.
Abstract : Normothermic machine perfusion presents a novel platform for pretransplant assessment and reconditioning of kidney grafts. Maintaining the metabolic activity of a preserved graft at physiologic levels requires an adequate oxygen supply, typically delivered by crystalloid solutions supplemented with red blood cells. In this study, we explored the feasibility of using a synthetic hemoglobin‐based oxygen carrier (HBOC) in human kidney normothermic perfusion. Fourteen discarded human kidneys were perfused for 6 hours at a mean temperature of 37°C using a pressure‐controlled system. Kidneys were perfused with a perfusion solution supplemented with either HBOC (n = 7) or packed red blood cells (PRBC) (n = 7) to increase oxygen‐carrying capacity. Renal artery resistance, oxygen extraction, metabolic activity, energy stores, and histological features were evaluated. Throughout perfusion, kidneys from both groups exhibited comparable behavior regarding vascular flow ( P  = .66), oxygen consumption ( P  = .88), and reconstitution of tissue adenosine triphosphate ( P  = .057). Lactic acid levels were significantly higher in kidneys perfused with PRBC ( P  = .007). Histological findings were comparable between groups, and there was no evidence of histological damage caused by the HBOC. This feasibility experiment demonstrates that a HBOC solution can offer a logistically more convenient off‐the‐shelf alternative to PRBC in normothermic machine perfusion of human kidneys. Abstract : An acellular oxygen carrier performs similarly to packed red blood cells during normothermic machine perfusion of human kidneys.